The Impact of Financial Literacy on Credit Card Usage and Repayment Behaviour in Malaysia - Chia, Hui Fang (2017)
Credit card has become a common mode of payment due to its readily available borrowing and payment functions that can help consumers cushion the impact of economic hardship and unexpected expenses. However, spending on credit cards has rapidly risen that worries about an over leveraged consumer economy are beginning to surface. Hence, it is vital to understand the fundamental of consumers’ financial decision in spending and borrowing. Financial decisions require the capacity to learn and understand financial concepts, including some complex ones. But how financially literate are consumers in Malaysia, in particular when it comes to credit card management? This dissertation aims to investigate the level of financial literacy among consumers in Malaysia and study its relationship to credit card management. The contribution of this dissertation is twofold: First, the results have demonstrated that majority of respondents display understanding in basic financial knowledge yet very few go beyond these basic concepts. Most importantly, our findings provide anecdotal evidence that both basic and credit card domain financial literacy have significant impact on credit card spending and repayment behaviour. Individuals with low level of financial literacy are more likely to engage in costly credit card behaviour. Second, we found that additional number of cards ownership and number of other loan commitments have significant influences on prudent credit card management. On the other hand, in terms of profiling credit card users in Malaysia, the findings revealed that older age group, higher education attainment, employed and self-employed individuals and higher income groups are more likely to have healthy credit card repayment behaviours.